2022
DOI: 10.48550/arxiv.2202.12157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gluon Fusion Production at NLO: Merging the Transverse Momentum and the High-Energy Expansions

Luigi Bellafronte,
Giuseppe Degrassi,
Pier Paolo Giardino
et al.

Abstract: The virtual corrections to gg → HH and gg → ZH are analytically evaluated combining an expansion in the small transverse momentum of the final particles with an expansion valid at high energies. The two expansion methods describe complementary regions of the phase space and we merge their results, extending the range of validity of both expansions using Padé approximants. We show that this approach can reproduce the available numerical results retaining the exact top quark mass dependence with an accuracy well… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The computation of the virtual corrections are based on the approach of Ref. [36], while for this work we have computed the real corrections and included them in a fast and flexible code. For the inclusive cross section, we have found that the NLO QCD corrections are of the same size as the LO contribution, and they increase the cross section by a factor of about 2.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The computation of the virtual corrections are based on the approach of Ref. [36], while for this work we have computed the real corrections and included them in a fast and flexible code. For the inclusive cross section, we have found that the NLO QCD corrections are of the same size as the LO contribution, and they increase the cross section by a factor of about 2.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the two-loop box integrals associated to A (1, ) i were evaluated combining two analytic approximations corresponding to different kinematical regimes, and here we briefly recall the main features of this approach, described in detail in Ref. [36].…”
Section: Concerning the Two-loop Form Factors Amentioning
confidence: 99%
See 3 more Smart Citations